2017
DOI: 10.3130/aija.82.1775
|View full text |Cite
|
Sign up to set email alerts
|

Verifying Vacancy Rates Derived From the Housing and Land Survey

Abstract: This study aims to verify statistical trends of the vacancy rate of Housing and Land survey, which may be exaggerated due to the following reasons: 1. Vacant houses of Housing and Land survey are judged by appearance. 2. Vacancy rates in surveys by the Ministry of Land, Infrastructure, Transport and Tourism, and the municipality are lower than that in Housing and Land survey. 3. The vacancy rates obtained from census and SUUMO-ZENRIN data are lower than that in Housing and Land survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Statistics that pertain to the number of vacant houses according to their status must be confirmed by the Housing and Land Survey of the Ministry of Internal Affairs and Communications; however, in these surveys, when no response survey slips can be obtained, the surveyors often judge whether the houses are vacant based on their appearance, and many have proposed that the ratio of vacant houses has been largely overestimated. 15) The factor of vacant houses has been highlighted in many previous studies. In a model for estimating the vacant house rate, Kanamori, Ariga, and Matsui 9) showed that the vacancy rate increases with the number of single-person households of people aged 65 years or older.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics that pertain to the number of vacant houses according to their status must be confirmed by the Housing and Land Survey of the Ministry of Internal Affairs and Communications; however, in these surveys, when no response survey slips can be obtained, the surveyors often judge whether the houses are vacant based on their appearance, and many have proposed that the ratio of vacant houses has been largely overestimated. 15) The factor of vacant houses has been highlighted in many previous studies. In a model for estimating the vacant house rate, Kanamori, Ariga, and Matsui 9) showed that the vacancy rate increases with the number of single-person households of people aged 65 years or older.…”
Section: Introductionmentioning
confidence: 99%